Transformation of Islamic Religious Education (PAI) Learning through an Emotional Approach - Naumi, Rufika; Suriana, Suriana; Nazila, Ukhwatun (ISTIFHAM, 2025)
The emotional approach in Islamic Religious Education (PAI) learning enhances students' understanding and motivation. Focusing solely on cognitive aspects is often less effective in shaping students' character and morals according to Islamic values. The emotional approach enables students to internalize Islamic values more deeply by engaging their feelings and personal experiences in learning. This study employs a literature review method by analyzing various scholarly sources discussing the emotional approach in PAI learning. The findings indicate that storytelling, experiential learning, and collective worship practices can increase students' emotional engagement, making learning more meaningful. Furthermore, a positive relationship between teachers and students and a school environment that supports Islamic values contributes to students' learning motivation. Therefore, the emotional approach should be more widely implemented in PAI learning to achieve more effective and impactful Islamic education.